The settlement of compensation in refarming of telecommunication spectrum: Case study of the 2600 MHz spectrum in Thailand - Rujirada Chaykaew (2018)
© Serials Publications Pvt. Ltd. The main purpose of this paper is to calculate the appropriate compensation amount for the refarming of the 2600 MHz spectrum in Thailand. Because the spectrum is limited in terms of resources, there is a lack of spectrum coverage for all operators. Moreover, some bands of spectrumhave not been used, making it useless and poor in terms of management. This problem can be solved by the National Broadcasting and Telecommunication Commission (NBTC) through spectrum refarming. As current, the NBTC aims to further develop the country by expanding and improving network coverage from 4G to 5G. This enables people in the countryto use a faster and better quality ofInternet system. However, the NBTC needs to use a larger spectrum as part of the telecommunications infrastructure in order to fully develop 5G. Therefore, the NBTC has to conduct spectrum refarming and the NBTC has to be compensatedforsuch spectrum refarming in respect of the factthat they currently hold this spectrum. This research study focuses only on the 2600 MHz spectrum as this is the best possible spectrum that can be refarmed in the near future. Currently, the Mass Communication Organization of Thailand (MCOT) holds this spectrum. Moreover, the MCOT has some other spectrum bandsthat have not been used. Therefore, this research aims to calculate the compensation for the refarming of the 2600 MHz spectrum. In this regard, the NBTC has to compensate the MCOTfor spectrum refarming. There are two sides considered to be part of this research, namely the MCOT and the NBTC. This research implements two methods in order to calculate the compensation amount: the "benchmarking method" and "full enterprise method". The full enterprise method is applicable to the NBTC and the benchmarking method is applicable to the MCOT. This research uses data obtained from ITU to calculate the compensation figure. A comparison is made between the data obtained from ITU and the data regarding the relative band value of the spectrum to find total revenue of 2600 MHz via the two methods. Afterthe researcher has obtained a total revenue amount that has been calculatedby using both methods, the researcher will then plot the value in a value line. After that, the researcher will look for an area of agreement between two sides. From the result, this research focuses on the result of the total revenue from 2019. The result from the full enterprise method (or NBTC's side) concludes that the total revenue is at THB 1, 288millionto1, 304million. This means that the NBTC has the ability (i.e. necessary funding) to pay the compensation for spectrum refarming in the range of THB 1, 288millionto1, 304million.The result from the benchmarking method (or MCOT's side), concludes that the total revenue is at THB 765 millionto775million. This means that the MCOT can agree and accept the compensation for spectrum refarming in range of THB 765 millionto775million. The result from this research, it is shown that the NBTC can successfully refarm the 2600 MHz spectrum from the MCOT. This is because the total revenue from the NBTC is higher than total revenue from the MCOT. Therefore, the NBTC and the MCOT are both satisfied with this outcome. The NBTC can agree on the compensation amountforthe refarming of 2600 MHz with the MCOT at the total of THB 775million. This is considered to be the area of agreement between the two sides. The results of this research can be used as a guideline for the projects of the NBTC forrefarming 2600 MHz.